Service user and caregiver involvement in mental health system strengthening in low- and middle-income countries: a cross-country qualitative study - Lempp, H. (Epidemiol Psychiatr Sci, 2017)
AIMS. The aims of this paper are to: (i) explore the experiences of involvement of mental health service users, their caregivers, mental health centre heads and policy makers in mental health system strengthening in three low- and middle-income countries (LMICs) (Ethiopia, Nepal and Nigeria); (ii) analyse the potential benefits and barriers of such involvement; and (iii) identify strategies required to achieve greater service user and caregiver participation. METHODS. A cross-country qualitative study was conducted, interviewing 83 stakeholders of mental health services. RESULTS. Our analysis showed that service user and caregiver involvement in the health system strengthening process was an alien concept for most participants. They reported very limited access to direct participation. Stigma and poverty were described as the main barriers for involvement. Several strategies were identified by participants to overcome existing hurdles to facilitate service user and caregiver involvement in the mental health system strengthening process, such as support to access treatment, mental health promotion and empowerment of service users. This study suggests that capacity building for service users, and strengthening of user groups would equip them to contribute meaningfully to policy development from informed perspectives. CONCLUSION. Involvement of service users and their caregivers in mental health decision-making is still in its infancy in LMICs. Effective strategies are required to overcome existing barriers, for example making funding more widely available for Ph.D. studies in participatory research with service users and caregivers to develop, implement and evaluate approaches to involvement that are locally and culturally acceptable in LMICs.